2003
DOI: 10.1073/pnas.0304533101
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring protein stability and aggregationin vivoby real-time fluorescent labeling

Abstract: In vivo fluorescent labeling of an expressed protein has enabled the observation of its stability and aggregation directly in bacterial cells. Mammalian cellular retinoic acid-binding protein I (CRABP I) was mutated to incorporate in a surface-exposed omega loop the sequence Cys-Cys-Gly-Pro-Cys-Cys, which binds specifically to a biarsenical fluorescein dye (FlAsH). Unfolding of labeled tetra-Cys CRABP I is accompanied by enhancement of FlAsH fluorescence, which made it possible to determine the free energy of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
239
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 226 publications
(253 citation statements)
references
References 34 publications
11
239
2
Order By: Relevance
“…Their main conclusion was that stability is unchanged in cells. The Gierasch laboratory fluorescently tagged cellular retinoic acid-binding protein I (16 kDA) in cells and measured stability by using urea denaturation (Ignatova and Gierasch 2004;Ignatova et al 2007). They showed that the test protein was destabilized in cells.…”
Section: Protein Stability In Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Their main conclusion was that stability is unchanged in cells. The Gierasch laboratory fluorescently tagged cellular retinoic acid-binding protein I (16 kDA) in cells and measured stability by using urea denaturation (Ignatova and Gierasch 2004;Ignatova et al 2007). They showed that the test protein was destabilized in cells.…”
Section: Protein Stability In Cellsmentioning
confidence: 99%
“…(We refer readers to their chapter in this volume for details.). They utilized the model to simulate the systems described above (Ghaemmaghami and Oas 2001;Ignatova and Gierasch 2004) using four scenarios. The first scenario considered only hard-core repulsions and, as predicted, the result was stabilization.…”
Section: Protein Stability In Cellsmentioning
confidence: 99%
“…The Ω-loop shows the lowest sequence conservation among the intracellular lipid-binding protein family (Gunasekaran et al, 2004) and tolerates sequence expansions and deletions (Ignatova and Gierasch, 2004). By this intramolecular insertion of the FlAsH-binding motif, we found that the FlAsH-fluorescence emission signal reports on the conformational state of the protein, with misfolded, denatured, and aggregated states hyperfluorescent compared to the native state (Ignatova and Gierasch, 2004). This system allowed us to measure in vivo stability using a urea titration (Ignatova and Gierasch, 2004;Ignatova et al, 2007a).…”
Section: A Design Of the Tetra-cys Protein Fluorescence Reporter Systemmentioning
confidence: 95%
“…Here we describe a fluorescence-based approach that we have recently developed to determine protein stability in vivo (in Escherichia coli cells) and in vitro (Ignatova and Gierasch, 2004) and that may be used to monitor in vivo folding propensities and aggregation kinetics in real time and in a noninvasive manner. The protein of interest is visualized in the context of all cellular macromolecules using the membrane-permeable bis-arsenical fluorescein-based dye "FlAsH" (named originally as a "fluorescein arsenical helix" binder), which specifically ligates to a genetically engineered, highly uncommon tetracysteine motif (Cys-Cys-Xxx-Yyy-CysCys) (Griffin et al, 2000).…”
Section: Rationalementioning
confidence: 99%
See 1 more Smart Citation